(untitled) (Journal of Medical Sciences, 2021)
The histological changes of uropygial gland (UG) were studied on 20 mature indigenous chickens during summer and winter seasons to highlight the significant function of the gland. The glands were collected by autopsy with a maximum of 0.5 cm thickness and fixed in 10% buffered formalin saline, followed by dehydration, then embedded into hard paraffin and sectioned at 3 µm, stained with special stains and examined under light microscope. The histological investigations showed that seasonal changes had a significant effect on weight and histological architectures of chicken UG. Grossly, the mass of the glands was larger in summer than winter samples. The surrounding capsule and glandular epithelium of summer were thinner with lower amount of adipose tissue, collagen and elastic fibers than winter. At uropygial papillae, the epithelium of secretory tubules of summer appeared thinner with wider lumen full of secretory contents than winter. However, some of winter samples showed accumulation of calcified granules in clumps at uropygial duct system and sinus which may indicated microbial infection. Histochemical changes of glands showed that PAS activity of summer was less intense in capsule, interlobular and secretory tubules than winter. Seasonal changes revealed that indigenous UG is more active which played a vital role during summer than winter season.